Relate North : Practising Place, Heritage, Art & Design for Creative Communities - Jokela, Timo; Coutts, Glen; Lapland University Press (fi=Lapland University Press|en=Lapland University Press|, 2017)
This book address issues ranging from the special conditions facing designers in the North and Arctic to the potential of art and science working together to raise awareness of plastic pollution in the sea and shorelines. The book explores contemporary practices in arts-based research and knowledge exchange in the fields of arts and design. By focusing on Northern and Arctic perspectives in contemporary art, design and education, the studies investigate issues of heritage, sustainability, socially engaged arts practice and socio-culturally sensitive research. acceptedVersion